Deep analysis of wild Vitis flower transcriptome reveals unexplored genome regions associated with sex specification - Ramos, Miguel Jesus Nunes (2017)
RNA-seq of Vitis during early stages of bud development, in male, female and hermaphrodite flowers, identified new loci outside of annotated gene models, suggesting their involvement in sex establishment. The molecular mechanisms responsible for flower sex specification remain unclear for most plant species. In the case of V. vinifera ssp. vinifera, it is not fully understood what determines hermaphroditism in the domesticated subspecies and male or female flowers in wild dioecious relatives (Vitis vinifera ssp. sylvestris). Here, we describe a de novo assembly of the transcriptome of three flower developmental stages from the three Vitis vinifera flower types. The validation of de novo assembly showed a correlation of 0.825. The main goals of this work were the identification of V. v. sylvestris exclusive transcripts and the characterization of differential gene expression during flower development. RNA from several flower developmental stages was used previously to generate Illumina sequence reads. Through a sequential de novo assembly strategy one comprehensive transcriptome comprising 95,516 non-redundant transcripts was assembled. From this dataset 81,064 transcripts were annotated to V. v. vinifera reference transcriptome and 11,084 were annotated against V. v. vinifera reference genome. Moreover, we found 3368 transcripts that could not be mapped to Vitis reference genome. From all the non-redundant transcripts that were assembled, bioinformatics analysis identified 133 specific of V. v. sylvestris and 516 transcripts differentially expressed among the three flower types. The detection of transcription from areas of the genome not currently annotated suggests active transcription of previously unannotated genomic loci during early stages of bud development.